Fragility analysis of a mass-timber frame structure with ring-doweled moment-resisting connections - Rodrigues, Leonardo (2018)
© WCTE 2018 Committee. The nonlinear behaviour of connections between structural elements is critical to the performance of mass-timber structures under seismic loads. However, limited work has been developed in nonlinear modelling and fragility assessment of mass-timber structures. To improve the accuracy of this approach, in particular when considering structures with ring-doweled moment-resisting connections, a nonlinear modelling approach and fragility assessment are proposed and a prototype example of a three-story building is analysed herein as a case study. For the case study, connections and members were designed following the prescriptions in Eurocode 5 and Eurocode 8, considering a high ductility structure. The mechanical properties of the structure are modelled as random variables to evaluate the impact of uncertainty on the prediction of the structural performance, in particular, on the probability of occurrence of ductile and brittle failure modes. The structure is studied under both nonlinear static analysis and multi-record incremental dynamic analysis. From these, fragility curves for different damage levels are computed and a q-factor is proposed. Results indicate that the requirements of Eurocode 5 and Eurocode 8 are sufficient to guarantee adequate performance for this type of structure, albeit these may be overconservative. Moreover, it is shown that uncertainties in material properties have a significant impact on the collapse capacity of these structures.